A reading of contemporary Arab critical thought discourse: epistemological questions and proposals. - Hadid, Asma (El Omda in Linguistics and Discourse Analysis, 2023)
Based on the issue of ‘epistemology’, this study questions the modern and contemporary Arab critique project for its epistemological identity, in the “critique of criticism” framework. There are various various problems concerning Arab criticism; the problem of translating and employing Western theories in reading Arabic texts, and the problem of method/ terminology and it's cultural and historical specifications. This is derived from the dilemma of theorization; which is the creative act related to the philosophical mind reference found in Western speeches. This reraises the epistemic question, concluding that the essence of the dilemma in Arab criticism is ontological-psychological.